Diagnostics of the achievements in mathematics of the fourth-formers gifted for the subject - Kiseliova, Danutė; Kiseliovas, Arkadijus (Lietuvos matematikos rinkinys, 2000)
The importance of primary school mathematics competitions as a fool in diagnostics of achievements in mathematics of the gifted in mathematics pupils studying at the highest education standard level has been emphasized. The results of 453 competition members and expertise of the competition tasks have been presented.